Adaptation to climate change in perennial cropping systems: Options, barriers and policy implications. Issue 82 (April 2018) - Gunathilaka, R.P.D.; Smart, James C.R.; Fleming, Christopher M.
Highlights: Information, firm size, elevation and climate are determining factors of adaptation. Experimenting with new adaptation options are prevented due to constraints. Adaptation policies should integrate with sustainable developmental goals. Abstract: Plantation crops are likely to be highly vulnerable to climate change because of their long economic life span, their typically non-irrigated cropping pattern and the inability to easily switch crops due to high upfront capital costs. Hence the sector requires appropriately designed adaptation options to cope with on-going climate change. Studies on climate adaptation in perennial cropping systems are rare relative to those on annual crops. Based on a cross-sectional survey of 50 tea estate managers representing all tea growing areas in Sri Lanka, this study analyses factors affecting choice of preferred adaptation options, barriers to adaptation and associated policy implications for tea production as an example of a perennial tree crop system. Current adaptation options identified are crop diversification, soil conservation, and shade tree establishment and management. All of these options are adopted in some situations and locations. All estate managers interviewed believe that climate change is happening and almost all are experiencing the negative impacts of climate change on tea production. Results from a multinomial logit analysis show that information on climate change, company size, tea growing elevation, and increases in temperature and rainfall are key factors influencing the preferred choice of adaptation option. Furthermore, results reveal that barriers such as a lack capital, inadequate access to near-term and medium-term climate knowledge, and poor governmental and institutional support may prevent estate managers from experimenting with new adaptation options. Policies should, therefore, be aimed at promoting new adaptation options through information exchange between a wide range of stakeholders, and integrating climate change adaptation with Sri Lanka's sustainable developmental goals. Governmental and institutional support and involvement would be instrumental in facilitating adoption of adaptation options such as joint-production of tea with valuable timber crops.